Congenital Left Ventricular Outpouchings: A Systematic Review of 839 Cases and Introduction of a Novel Classification after Two Centuries. (27th August 2014) - Malakan Rad, Elaheh; Awad, Sawsan; Hijazi, Ziyad M.
Abstract Background Congenital left ventricular outpouchings (LVOs) are reported under five overlapping and poorly defined terms including left ventricular accessory chamber, left ventricular aneurysm (LVA), left ventricular diverticulum (LVD), double‐chambered LV, and accessory left ventricle. Diagnostic criteria are frequently mixed and not mutually exclusive. They convey no information regarding treatment strategy and prognosis. Objectives The aim of this systematic review is to provide a clear and inclusive classification, with therapeutic and prognostic implications, for congenital LVOs. Data sources We performed three separate sets of search on three subjects including "congenital left ventricular outpouchings, " "important and simply measurable markers of left ventricular function, " and "relationship of mechanics of intraventricular blood flow and optimal vortex formation in left ventricle and elliptical geometry of LV." Study eligibility criteria We enrolled case series, review articles, and case reports with literature review. All types of acquired LVO's were excluded. Study appraisal and synthesis methods We studied the abstracts of all searched articles. We focused on diagnostic criteria and patients' outcome. To examine the validity and reliability of the novel classification, fifteen previous studies were revisited using the novel classification. Results A total of 20 papers from 11 countries fulfilled our inclusion criteria. The age of patients ranged from prenatal age to geriatric age range. Diagnostic criteria were clearly stated only for two of the above five terms (i.e., congenital LVA and congenital LVD). Cases with mixed diagnostic criteria were frequent.Elliptical geometry of left ventricle was found to have significant impact on effective blood flow mechanics in LV. A simple inclusive classification for congenital LVOs, with therapeutic and prognostic implications, was introduced. Conclusion The cornerstone of this classification is elliptical LV geometry. Large‐type IIc LVO have dismal prognosis, if left untreated. LVO type I and small LVO type IIa have the best prognosis.